2003
DOI: 10.1046/j.1365-3040.2003.00994.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic limitations in olive cultivars with different sensitivity to salt stress

Abstract: Olive ( Olea europea L) is one of the most valuable and widespread fruit trees in the Mediterranean area. To breed olive for resistance to salinity, an environmental constraint typical of the Mediterranean, is an important goal. The photosynthetic limitations associated with salt stress caused by irrigation with saline (200 m M ) water were assessed with simultaneous gas-exchange and fluorescence field measurements in six olive cultivars. Cultivars were found to possess inherently different photosynthesis when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
146
0
6

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(172 citation statements)
references
References 23 publications
16
146
0
6
Order By: Relevance
“…Nevertheless, patchy stomatal closure [6] and changes in cuticular [5] and g m [7] must be considered. There is an increasing body of evidence indicating that g m decreases in response to drought and salinity [11,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, patchy stomatal closure [6] and changes in cuticular [5] and g m [7] must be considered. There is an increasing body of evidence indicating that g m decreases in response to drought and salinity [11,13,20].…”
Section: Discussionmentioning
confidence: 99%
“…The rapid increase suggested that ABA was synthesized in situ rather than transported from the roots. In addition, salt stress also can reduce the mesophyll conductance to CO 2 , and then result in the decrease of photosynthetic rate (Loreto et al 2003). The resistance of the chloroplast envelope and stroma is mainly responsible for the total mesophyll resistance, and it is also influenced by respiratory and photorespiratory CO 2 diffusing toward the chloroplasts from the mitochondria (Tholen et al 2012).…”
Section: Plant Biomass and Photosynthesismentioning
confidence: 99%
“…All these studied traits were decreased with increasing salinity. Plants growing under saline condition remain stunted due to reduction in cell elongation and cell division, which are under the control of different auxins, whose synthesis is retarded by the salinity (Loreto et al 2003;Ndayiragije and Lutts 2006). The reduction in biomass increased with the increase exposure of salinity, because of disturbances in physiological and biochemical activities under saline conditions (Craine 2005;Munns et al 2006) that may be due to the reduction in leaf area and number of leaves (Romero-Aranda et al 1998;Dong et al 2007).…”
Section: Resultsmentioning
confidence: 99%